Cannabidiol and Terpene Formulation Reducing SARS-CoV-2 Infectivity Tackling a Therapeutic Strategy - Santos, Susana; Barata, Pedro; Charmier, Adilia; Lehmann, Inês; Rodrigues, Suzilaine; Melosini, Matteo M.; Pais, Patrick J.; Sousa, André P.; Teixeira, Catarina; Santos, Inês; Rocha, Ana Catarina; Baylina, Pilar; et al. (Frontiers in Immunology, 2022)
In late 2019, CoViD-19 emerged in Wuhan, China. Currently, is an ongoing global health threat stressing the need for therapeutic compounds. Linking the virus life cycle and its interaction with cell receptors and internal cellular machinery is key for developing therapies based on the control of infectivity and inflammation. In this framework, we evaluate the combination of cannabidiol (CBD), as an anti-inflammatory molecule, and terpenes, by their anti-microbiological properties, in reducing SARS-CoV-2 infectivity. Our group settled six formulations combining CBD and terpenes purified from Cannabis sativa L, Origanum vulgare and Thymus mastichina. The formulations were analyzed by HPLC and GC-MS and evaluated for virucide and anti-viral potential by in vitro studies in alveolar basal epithelial, colon, kidney, and keratinocytes human cell lines. Conclusions and impact: We demonstrate the virucide effectiveness of CBD and terpenes-based formulations. F2TC reduces the infectivity by 17%, 24% and 99% for CaCo-2, HaCat and A549 respectively and F1TC by 43%, 37% and 29% for Hek293T, HaCaT and Caco-2. To the best of our knowledge, this is the first approach that tackles the combination of CBD with a specific group of terpenes against SARS-CoV-2 in different cell lines. The differential effectiveness of formulations according to the cell line can be relevant to understanding the pattern of virus infectivity and the host inflammation response, and lead to new therapeutic strategies